2017
DOI: 10.26701/ems.356823
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Experimental Mechanical Properties and DMA Measurement of Nanoclay Hybrid Composites

Abstract: This study explores the effects of nanoclay addition on mechanical response of Glass/Carbon/Glass fiber (G/C/G) reinforced epoxy matrix composite laminates under tensile and flexural loadings. Organomodified nanoclay containing Glass/Carbon/Glass hybrid composite laminate was evaluated for dynamic mechanical properties as well as mechanical strength, stiffness and ductility. Three different weight fractions of nanoclay containing fiber reinforced hybrid composites were manufactured. The amount of nanoclay addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…This indicates that the stiffness is remarkably enhanced by the increased CuNP content of the monofilament [16]. Ünal et al also reported a similar phenomenon in nanoclay containing fiber-reinforced hybrid composites [33].…”
Section: Viscoelastic Propertiesmentioning
confidence: 80%
“…This indicates that the stiffness is remarkably enhanced by the increased CuNP content of the monofilament [16]. Ünal et al also reported a similar phenomenon in nanoclay containing fiber-reinforced hybrid composites [33].…”
Section: Viscoelastic Propertiesmentioning
confidence: 80%
“…This may be due to less crosslinking density between the clay layers or the varying stoichiometry between the epoxy and the curing agent 61,62 . In contrast, some studies have reported a decrease or almost a slight increase in T g 63,64 …”
Section: Resultsmentioning
confidence: 98%
“…61,62 In contrast, some studies have reported a decrease or almost a slight increase in T g . 63,64 In general, the water uptake of a composite system depends on several factors, for example, the hydrophilic or hydrophobic nature of the matrix and the filler, the interfacial adhesion between the filler and the matrix, and the voids in the composite structure. 65 It is important to determine the water absorption properties of materials because it is known that water absorption of polymers causes plasticization, deteriorates their mechanical properties (modulus of elasticity, tensile, and other strengths), and causes hydrothermal degradation (e.g., microcracks).…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…In Figure 10 c, the storage module of the ABS nanocomposites is shown, in which it can be observed that the ABS/0.25CNC C150 nanocomposite presented the highest elastic modulus in relation to pure ABS. Young’s modulus values evaluated through stress tests were much lower than the storage modulus determined by DMA, possibly because the material was not completely isotropic and in addition to the fact that stress was not applied to the direction of the specimen [ 39 ].…”
Section: Resultsmentioning
confidence: 99%